2022
DOI: 10.1101/2022.02.28.481642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden diversity – DNA metabarcoding reveals hyper-diverse benthic invertebrate communities

Abstract: Freshwater ecosystems, such as streams, are facing increasing pressures from agricultural land use. Aquatic insects and other macroinvertebrates have historically been used as indicators of ecological condition and water quality in freshwater biomonitoring programs; however, many of these protocols use coarse taxonomic resolution (e.g., family) when identifying macroinvertebrates. The use of family-level identification can mask species-level diversity, as well as patterns in community composition in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Streams are very heterogenous habitats and support many rare species, which can make it challenging to describe patterns in invertebrate distributions (Heino et al, 2015). Previous research using DNA metabarcoding in Ontario streams supported this description of heterogenous streams as aquatic macroinvertebrate communities were highly variable within a single stretch and largely composed of rare OTUs (Gleason et al 2022). However, while Heino et al (2015) detected only weak relationships between environmental and spatial factors and macroinvertebrate community structure at genus-level resolution, we found significant relationships between all variables (local, regional, spatial) even though DNA metabarcoding increases the number of rare taxa detected.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Streams are very heterogenous habitats and support many rare species, which can make it challenging to describe patterns in invertebrate distributions (Heino et al, 2015). Previous research using DNA metabarcoding in Ontario streams supported this description of heterogenous streams as aquatic macroinvertebrate communities were highly variable within a single stretch and largely composed of rare OTUs (Gleason et al 2022). However, while Heino et al (2015) detected only weak relationships between environmental and spatial factors and macroinvertebrate community structure at genus-level resolution, we found significant relationships between all variables (local, regional, spatial) even though DNA metabarcoding increases the number of rare taxa detected.…”
Section: Discussionmentioning
confidence: 69%
“…However, Noguerales et al (2021) found that both environmental filtering and spatial arrangement were important structuring components of soil invertebrates. These studies illustrate the applicability of DNA metabarcoding for metacommunity ecology, and a key uncertainty which remains is how metacommunity dynamics change in response to agriculture in stream systems where 1) there are no discrete community boundaries and 2) community composition can vary drastically at small spatial scales (Gleason et al, 2022).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations